Mesothelial cells derived extracellular vesicles promote angiogenesis through the transfer of angiopoietin-2 - Shelly Loewenstein; Fabian Gerstenhaber; Sapir Milshtain; Stav Leibou; Omri Rahamimov; Alison Siegel; Hannah Sherman; Osnat Sher; Guy Lahat (PLoS ONE, 2026)
Background Peritoneal mesothelial cells play a critical role in shaping the peritoneal tumor microenvironment and are increasingly recognized as active regulators of angiogenesis in cancers that metastasize to the peritoneum, including gastrointestinal (GI) and ovarian malignancies. Through complex interactions with tumor and stromal cells, peritoneal mesothelial cells contribute to the establishment of a pre-metastatic niche in the peritoneal cavity. Extracellular vesicles (EVs), nanosized vesicles secreted by most cell types, mediate intercellular communication by transferring bioactive molecules such as proteins, lipids, and nucleic acids. While tumor-derived EVs have been extensively studied in cancer progression, the role of mesothelial cells-derived EVs in regulating endothelial function and angiogenesis remains largely unexplored. Methods EVs were isolated from conditioned media of mesothelial cells and characterized before functional assays. Their effects on endothelial cell behavior were assessed using proliferation, migration, and invasion assays, as well as Matrigel-based tube formation and in vivo angiogenesis plug models. A proteome profiler angiogenesis array was used to identify enriched pro-angiogenic mediators. Mechanistic studies were conducted using lentiviral knockdown and overexpression strategies. Results Endothelial cells efficiently internalized mesothelial cells-derived EVs, leading to significant increases in proliferation, migration, invasion, and angiogenesis in vitro and in vivo. Proteomic profiling identified 43 angiogenic regulators within mesothelial cells-derived EVs, with angiopoietin-2 (ANG2) emerging as a key effector. Functional analyses demonstrated that mesothelial cells-derived EVs-induced angiogenesis was mediated through ANG2-TIE2 signaling, with subsequent activation of PI3K, Akt, and ERK1/2 pathways. Importantly, inhibition of ANG2 markedly reduced these angiogenic effects. Conclusions This work establishes that EVs secreted by mesothelial cells promote angiogenesis by reprogramming endothelial cells through ANG2-dependent signaling. These findings uncover a novel mechanism of mesothelial-endothelial communication and highlight the ANG2 pathway as a promising therapeutic target in advanced GI cancers with peritoneal metastasis.